Anguish, sensuality and female confrontation in Gabriela Cravo e Canela (TEL Tempo, Espaço e Linguagem, 2022)
The aim of the article is to discuss the suffering of the protagonist of Gabriela Cravo e Canela (1958), by Jorge Amado. The method is the theoretical and interpretive essay and elements of violence against women and patriarchal culture are discussed. Observed that power relations, evaluative and sexist judgments produced anguish in the protagonist and made her position herself in defense of the singularity of her desire.